Emotional Competences in University and Teachers: A Systematic Review - Ana Cecilia VÃ¡squez MIRANDA; DariÃ©n Barramedo RodrÃguez GALAN; Johnny FÃ©lix FarfÃ¡n PIMENTEL (International Journal of Environmental, Sustainability, and Social Science, 2021)
The aim of the review is to analyze the impact of emotional competence in the context of the university curriculum and therefore on teachers. The study was developed under the parameters of the PRISMA declaration, the compilation of information was carried out mainly in scientific databases such as Scopus, Proquest and Ebsco; using key search terms such as â€œemotional skills and educationâ€, â€œemotional skills in teachersâ€, â€œemotional skills and trainingâ€ among others which made it possible to find theories and possible scientific results to serve as the basis for the current study. Research period 2017 to 2020 Inclusion criteria: research articles, systematic reviews and case studies; peer-reviewed, linked or intertwined with emotional competence in students and teachers Exclusion criteria: investigations that were not subject to peer review, with methodological deficiencies or which did not show a relationship or linkage with the stated categories. As a result, 19 (out of 155 returned by a global search) studies that met the inclusion criteria were included. These results allow us to conclude that emotions and educational success have determined factors in the development of emotional competence of students and teachers; need to build learning scenarios that encourage emotional management and connection with others.